翻訳と辞書
Words near each other
・ Feyenoord Jubilee Tournament
・ Feyenoord Tournament
・ Feyer
・ Feyerabend
・ Feyerharm Knoll
・ Feyerick
・ Feyhaman Duran
・ Feyisa Lilesa
・ Feyli
・ Feyli Kurds
・ Feylinia
・ Feynman (disambiguation)
・ Feynman checkerboard
・ Feynman diagram
・ Feynman Long Division Puzzle
Feynman parametrization
・ Feynman point
・ Feynman slash notation
・ Feynman sprinkler
・ Feynman's Lost Lecture
・ Feynman–Kac formula
・ Feyntje Steenkiste
・ Feynuus FC
・ Feyr
・ Feyrouz
・ Feyrouz (actress)
・ Feys
・ Feyse Tadese
・ Feysville, Western Australia
・ Feyt


Dictionary Lists
翻訳と辞書 辞書検索 [ 開発暫定版 ]
スポンサード リンク

Feynman parametrization : ウィキペディア英語版
Feynman parametrization
Feynman parametrization is a technique for evaluating loop integrals which arise from Feynman diagrams with one or more loops. However, it is sometimes useful in integration in areas of pure mathematics as well.
Richard Feynman observed that:
:\frac=\int^1_0 \frac
which simplifies evaluating integrals like:
:\int \frac=\int dp \int^1_0 \frac=\int^1_0 du \int \frac.
More generally, using the Dirac delta function:
:\begin
\frac&=(n-1)!\int^1_0 du_1 \cdots \int^1_0 du_n \frac \\
&=(n-1)! \int^1_0 du_1 \int^_0 du_2 \cdots \int^ \frac">(A_n-A_)\right )^n}.
\end
Even more generally, provided that \text ( \alpha_ ) > 0 for all 1 \leq j \leq n :
:\frac}\cdots A_^=\frac)})}\int_^du_\cdots\int_^du_\fracu_-1)u_^\cdots u_^}+\cdots+u_A_\right" TITLE="u_A_+\cdots+u_A_\right">)^\alpha_}}
. 〔

See also Schwinger parametrization.
==Derivation==
:\frac = \frac\left(\frac-\frac\right)=\frac\int_B^A \frac.
Now just linearly transform the integral using the substitution,
:u=(z-B)/(A-B) which leads to du = dz/(A-B) so z = uA + (1-u)B
and we get the desired result:
:\frac = \int_0^1 \frac.
In more general cases, derivations can be done very efficiently using the Schwinger parametrization. For example, in order to derive the Feynman parametrized form of : \frac , we first reexpress all the factors in the denominator in their Schwinger parametrized form:
:\frac= \int^\infty_0 ds_i \, e^, \forall i =1,...,n
and rewrite,
:
\frac=\int_0^\infty ds_1...ds_n \exp\left().

Then we perform the following change of integration variables,
:
\alpha = s_1+...+s_n,

:
\alpha_ = \frac; i=1,\ldots,n-1,

to obtain,
:
\frac = \int_^d\alpha_1...d\alpha_ \int_^d\alpha \alpha^\exp\left(-\alpha\left\+ \left(1-\alpha_-...\alpha_\right)A_\right\} \right).

The next step is to perform the \alpha integration.
:
\int_^d\alpha \alpha^\exp(-\alpha x)= \frac}\left(\int_^d\alpha\exp(-\alpha x)\right)=\fracA_+ \left(1-\alpha_-...\alpha_\right)A_.
Substituting this result, we get to the penultimate form,
:
\frac=\left(n-1\right)!\int_^d\alpha_1...d\alpha_\frac+" TITLE="\alpha_1A_1+...+\alpha_A_+">\left(1-\alpha_-...\alpha_\right)A_ )^n} ,

and, after introducing an extra integral, we arrive at the final form of the Feynman parametrization, namely,
:
\frac=\left(n-1\right)!\int_^d\alpha_1...d\alpha_\frac" TITLE="\alpha_1A_1+...+\alpha_A_">)^n} .

Similarly, in order to derive the Feynman parametrization form of the most general case, : \frac} one could begin with the suitable different Schwinger parametrization form of factors in the denominator, namely,

:
\frac\int^\infty_0 ds_1 \,s_1^ e^ = \frac\frac}\left(\int_^ds_1 e^\right)

and then proceed exactly along the lines of previous case.

抄文引用元・出典: フリー百科事典『 ウィキペディア(Wikipedia)
ウィキペディアで「Feynman parametrization」の詳細全文を読む



スポンサード リンク
翻訳と辞書 : 翻訳のためのインターネットリソース

Copyright(C) kotoba.ne.jp 1997-2016. All Rights Reserved.